Reconfiguration of Upper Airway Stimulation Devices Utilizing Awake Endoscopy. (25th February 2020) - Meleca, Joseph B.; Kominsky, Alan H.
Abstract : Objectives: Determine the rates of, reasons for, and effectiveness of device reprogramming utilizing in‐office awake endoscopy (AE) in subjects who underwent upper airway stimulation (UAS) surgery. Study Design: Retrospective chart review. Methods: Retrospective chart review at a tertiary care center on patients implanted with UAS devices from November 2015 to July 2018. Results: Sixty patients were implanted with UAS devices. Average pre‐ and postsurgical total apnea–hypopnea index (AHI) was 40.6 and 4.2 with a 36.4 total AHI reduction. Treatment success based on Sher criteria was observed in 88% of patients. Postoperative titration polysomnography revealed an average functional threshold (FT) and minimum therapeutic amplitude (MTA) of 1.6 and 2.1 V, respectively. A total of 24 AEs were performed in 19 (32%) patients. The most common complaints and reasons for AE were perceived stimulus discomfort (42%), frequent awakenings (32%), and persistent fatigue or non‐normalized AHI (21%). After first AE, there was a 0.87 (53%) and 0.93 (45%) V reduction in FT and MTA, respectively. Conclusion: Patients with obstructive sleep apnea continue to succeed with UAS. Fewer than one‐third of patients had postsurgical complaints requiring device reconfiguration utilizing AE to assess the pharyngeal airway and optimize device settings. Reduction in the FT and MTA after AE may improve compliance by reducing discomfort and frequent awakenings. Periodic monitoring of patients with implanted UAS devices is necessary to optimize efficacy and maintain patient compliance. Level of Evidence: 4 Laryngoscope, 130:2494–2498, 2020